Dipoena castrata Bosenberg & Strand 1906 - Marusik, Yuri M.; Koponen, Seppo (Zenodo, 2000)
Dipoena castrata Bosenberg & Strand, 1906 ** Chikuni, 1989: 36, f. 30; Song et al., 1999: f. 53i-j, n-o. Material examined: 2 ♀♀ [21] Khasan Distr, env. of Andreevka Vill, 42º35-36'N 131º13'E, 11- 15.08.1998, YM COMMENTS. The first record in Russia. In addition to the Maritime Province, found also in Kunashir and South Sakhalin (Marusik, personal data). Known from Liaoning & Jilin, China [Songet al., 1999], Korea and almost entire Japan [Yaginuma, 1977], : Published as part of Marusik, Yuri M. & Koponen, Seppo, 2000, New data on spiders (Aranei) from the Maritime Province, Russian Far East, pp. 55-68 in Arthropoda Selecta 9 (1) on page 65, DOI: 10.5281/zenodo.822713 : {"references": ["Chikuni Y. 1989. Pictorial encyclopedia of spiders in Japan. Tokyo: Kaiseisha Publ. 308 pp. [in Japanese]", "Song DX, Zhu, M. S, Chen, J. 1999. The spiders of China. Hebei Science & Technology Press. 640 pp.", "Yaginuma T. 1977. A list of Japanese spiders (revised in 1977) / / Acta Arachnol. Vol. 27. Spec. No. P. 367 - 406."]}